Pengaruh Materi Sekolah Minggu terhadap Perilaku Anak Sekolah Minggu di GKPS Marubun Lokkung Tahun 2025 - Thabita Mutiara; Nisma simorangkir; Dorlan Naibaho; Ibelala Gea; Raykapoor Raykapoor (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study was to determine the Effect of Sunday School Material on the Behavior of Sunday School Children at GKPS Marubun Lokkung 2025. The method used in this study is a quantitative method. The population used by the researcher was the total number of Sunday school children aged 8 to 11 years at the GKPS Marubun Lokkung Church in 2025 as many as 30 people and the sample in the study was all populations totaling 30 people. Data were collected using a positive closed questionnaire of 30 items. The results of data analysis show that there is an Influence of Sunday School Materials on the Behavior of Sunday School Children at GKPS Marubun Lokkung 2025: 1) Analysis requirements test: a) A positive relationship test is obtained by the value of the Influence of Sunday School Materials on the Behavior of Sunday School Children at GKPS Marubun Lokkung 2025. rxy = 0.621> rtable (α = 0.05; n = 30) = 0.361 thus it is known that there is a positive relationship between variable X and variable Y. b) A significant relationship test is obtained by tcount = 5.322> rtable (α = 0.05; n = 28) = 2.048 thus there is a significant relationship between variable X and variable Y. Thus Ha is accepted and H0 is rejected.